1977
DOI: 10.1104/pp.60.3.407
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Utilization of Sugar Phosphates by Anabaena flos-aquae

Abstract: The effect of various sugar phosphates on CO2 fixation in Anabacna flos-aquae was investigated and found to be very smilar to that found for isolated spinch chloroplasts. One exception, glucose 6-phosphate, has a stimulatory effect on CO2 fixation in Anabena but not in isolated chloroplast.Further examination of the role of glucose 6-phosphate metabolsm in The generally obligate nature of photoautotrophic growth in the blue-green algae has prompted the investigation of the biochemical basis for this growth hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The energetics of the glucose transport system of Prochlorococcus SS120 was also studied. Our initial hypothesis considered that glucose uptake could be most useful for Prochlorococcus under energy-limited conditions; however, we have shown that the glucose uptake rate was higher under light, with a circa 40% decrease when cells were subjected to darkness ( Gómez-Baena et al, 2008 ), in accordance with what has been described in previous studies on uptake of organic compounds ( Rubin et al, 1977 ; Church et al, 2004 , 2006 ; Michelou et al, 2007 ; Mary et al, 2008 ; Talarmin et al, 2011 ; Gómez-Pereira et al, 2013 ; Bjorkman et al, 2015 ). To evaluate if GlcH is a primary or secondary active transporter, we used different inhibitors of active transport to evaluate if GlcH is a primary or secondary active transporter (i.e., uses energy provided by ATP or from ionic gradients in order to take up glucose, respectively), namely monensin, valinomycin, DCCD, and CCCP.…”
Section: Resultssupporting
confidence: 89%
“…The energetics of the glucose transport system of Prochlorococcus SS120 was also studied. Our initial hypothesis considered that glucose uptake could be most useful for Prochlorococcus under energy-limited conditions; however, we have shown that the glucose uptake rate was higher under light, with a circa 40% decrease when cells were subjected to darkness ( Gómez-Baena et al, 2008 ), in accordance with what has been described in previous studies on uptake of organic compounds ( Rubin et al, 1977 ; Church et al, 2004 , 2006 ; Michelou et al, 2007 ; Mary et al, 2008 ; Talarmin et al, 2011 ; Gómez-Pereira et al, 2013 ; Bjorkman et al, 2015 ). To evaluate if GlcH is a primary or secondary active transporter, we used different inhibitors of active transport to evaluate if GlcH is a primary or secondary active transporter (i.e., uses energy provided by ATP or from ionic gradients in order to take up glucose, respectively), namely monensin, valinomycin, DCCD, and CCCP.…”
Section: Resultssupporting
confidence: 89%
“…40% decrease when cells were subjected to darkness. In good agreement with these results, light also enhances the uptake of sugars in other cyanobacteria [28] , [29] , and that of amino acids in Prochlorococcus (50% increase) [13] , [29] .…”
Section: Resultssupporting
confidence: 84%
“…Anabaena sp. are notoriously hard to phosphate starve and it make take weeks to drive them to P starvation in culture (Rubin et al, 1977;Whitton et al, 1991). By analogy with the closely related Anabaena sp., we infer that Aphanizomenon sp.…”
Section: Dissolved Inorganic-p Threshold For Alkaline Phosphatase Actmentioning
confidence: 99%
“…Therefore, even when orthophosphate becomes depleted from the environment, organisms able to produce alkaline phosphatase will not be Plimited, but may be phosphate-deficient. Phosphate-deficiency is defined as the condition in which extracellular orthophosphate concentrations drop to levels at which cells can no longer maintain intracellular surplus-P. Phytoplankton have the ability to store surplus-P in the form of polyphosphates (polymers of orthophosphate) (Rubin et al, 1977;Reynolds, 1984). The mechanism by which surplus-P storage occurs is defined as luxury uptake.…”
Section: Phosphorus-versus Phosphate-deficiencymentioning
confidence: 99%